2010
DOI: 10.1111/j.1365-2435.2010.01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness consequences of immune responses: strengthening the empirical framework for ecoimmunology

Abstract: Summary 1.Ecoimmunologists aim to understand the costs, benefits, and net fitness consequences of different strategies for immune defense. 2. Measuring the fitness consequences of immune responses is difficult, partly because of complex relationships between host fitness and the within-host density of parasites and immunological cells or molecules. In particular, neither the strongest immune responses nor the lowest parasite densities necessarily maximize host fitness. 3. Here, we propose that ecoimmunologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
253
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(258 citation statements)
references
References 92 publications
(195 reference statements)
5
253
0
Order By: Relevance
“…As emphasized in several recent articles, higher immunological response does not necessarily indicate a better parasite resistance or even better lifetime health (Owen and Clayton, 2007;Graham et al, 2011). On the contrary, higher immune response may even indicate ineffective antiparasite protection or immunopathology (Graham et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…As emphasized in several recent articles, higher immunological response does not necessarily indicate a better parasite resistance or even better lifetime health (Owen and Clayton, 2007;Graham et al, 2011). On the contrary, higher immune response may even indicate ineffective antiparasite protection or immunopathology (Graham et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with our findings of relatively normal transcription of AHR, Bodkin et al (2012) indicated that average annual oil encounter rates ranged from 2 to 24 times yr −1 for females, and 2 to 4 times yr −1 for males. Mitigation of detrimental effects imposes demands on animals above those normally required to sustain life and may result in reduction of fitness evidenced by decreased reproductive capability, increased susceptibility to disease, or disadvantageous behavioral changes (Graham et al 2010, Martin et al 2010. Such effects may ultimately be manifested in reduced survival rates , Monson et al 2011) that contributed to the delayed recovery of sea otters observed in areas of PWS initially oiled in 1989 (Bodkin et al 2002).…”
Section: Statistical Clustersmentioning
confidence: 99%
“…Chronic transcription of genes responsible for immunologic function, including detoxification, can be physiologically costly (Graham et al 2010). Perhaps the largest cost is the reallocation of nutrients and energy from one portion of an individual's resource budget to other functions.…”
Section: Statistical Clustersmentioning
confidence: 99%
“…House sparrows appear prone to hyper-inflammation over long periods in captivity ( enhancements might be interpreted as protective, these elevations are more likely indicative of immune disregulation with subsequent, strong negative impacts (i.e. immunopathology) on hosts (Graham et al, 2011). In the present study, we examined captivity effects on two innate immune measures: BKA (Millet et al, 2007) and oxidative burst (Sepp et al, 2010;Sild and Horak, 2010).…”
Section: Captivity Effects On Immune Functionsmentioning
confidence: 99%
“…immunopathology) on hosts (Graham et al, 2011). In the present study, we examined captivity effects on two innate immune measures: BKA (Millet et al, 2007) and oxidative burst (Sepp et al, 2010;Sild and Horak, 2010).…”
Section: The Journal Of Experimental Biology the Journal Of Experimenmentioning
confidence: 99%